Tanggung Jawab Negara Terhadap Sampah Ruang Angkasa Menurut Hukum Internasional - Frijan Masa'i; Afrizal Vatikawa; Annisa Novia Indra Putri Putri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
Due to a lot of garbage, celestial bodies crashing into satellites are no longer a common thing. Even on March 12, 2017, the International Space Station (ISS) was almost hit by a shard of a celestial body whose diameter is only 0.8 centimeters but has a speed of 30,000 km per hour. The study aims to explain the responsibility of the fall of space waste to other countries according to international law. The impact of such use can interfere with the sovereignty of the country's territory, so that the International Law Commission (ILC), which is a United Nations Agency tasked with managing and discussing drafts on provisions on state responsibility, issues international legal instruments on state responsibility and this instrument is only related to state responsibility with general principles which is called as the Responsibility of States for Internationally Wrongful Acts (ILC ASR). If space debris falls to earth and enters the territory of another country, then we can conclude that the country that owns the space waste must be responsible for the country that falls into the space waste even though it is not the fault of the operator or the country that owns the satellite.